Guasistationary process conditions of extrusion elastomeric materials on single-screw extruders - M. M. Grigorieva; D. B. Gorbunov; A. A. Tatarnikov (Тонкие химические технологии)
The design procedure of a time characteristic of a single-screw extruder on the channel «a food - productivity» is developed at processing of elastomeric materials. The technique allows to estimate a filtrating ability of a pressure head zone